Patients with chronic hepatitis B treated with oral antiviral therapy retain a higher risk for HCC compared with patients with inactive stage disease. Issue 12 (10th March 2014) - Cho, Ju-Yeon; Paik, Yong-Han; Sohn, Won; Cho, Hyun Chin; Gwak, Geum-Youn; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul
Abstract : Background: It is generally stated that oral antiviral therapy in patients with chronic hepatitis B (CHB) decreases the risk of developing hepatocellular carcinoma (HCC). Although oral nucleos(t)ide analogues (NUCs) may induce a state similar to inactive stage CHB, the long-term risk for HCC in patients treated with NUCs compared with inactive CHB is unclear. Methods: A total of 1378 patients who were treatment naïve and started NUC therapy and 1014 patients with inactive stage CHB who were HBeAg-negative and continuously had hepatitis B DNA <2000 IU/mL during follow-up were enrolled. The NUC group was divided into two groups by continuous viral suppression: NUC complete responder (CR) group and NUC incomplete responder (IR) group. Cumulative HCC incidence rates were compared between the groups. Results: The risk of developing HCC was significantly higher in the NUC CR group compared with the inactive CHB group, regardless of the presence of baseline liver cirrhosis (p<0.001). Risk factors associated with the development of HCC were treatment groups (p<0.001), age (p<0.001), sex (p<0.001) and the presence of liver cirrhosis at baseline (p=0.005). Of the NUC group, the cumulative incidence of HCC in the NUC IR group was significantly higher compared with the NUC CR group (p=0.028). Conclusions: The use of potent oral antiviral therapy can effectively suppress HBV replication in patients with CHB. However, the risk of HCC development in patients treated with oral antiviral agent is still significantly higher than patients with inactive stage CHB.